Women Empowerment Through Non-Governmental Organizations’ Programs in Shiraz, Iran - Nikkhah, Hedayat Allah (2010)
The purpose of this study was to investigate the effect of NGOs‟ functions and activities on women‟s empowerment. The study also aimed to determine various impacts of approaches used by NGOs (top-down, partnership, and bottom-up) on empowerment.This study measured two levels of empowerment: individual and collective (community)empowerment. Data were collected from eleven women‟s NGOs comprising one hundred and ninety five (195) women who supported by these NGOs in Shiraz. This study employed the survey method with self-administrated questionnaires to answer several questions about individual and community empowerment of women. In-depth interviewalso, was applied to collect information about the NGOs in order to identify the NGOs activities, functions and its approaches. This study discovers that the activities of NGOs in Shiraz can be categorized into four functions: „developing individual ability‟; „educational functions‟; „awareness building‟;„mobilizing women to participate‟. The results were analyzed using some statistics i.e.,The purpose of this study was to investigate the effect of NGOs‟ functions and activities on women‟s empowerment. The study also aimed to determine various impacts of approaches used by NGOs (top-down, partnership, and bottom-up) on empowerment. This study measured two levels of empowerment: individual and collective (community)empowerment. Data were collected from eleven women‟s NGOs comprising one hundred and ninety five (195) women who supported by these NGOs in Shiraz. This study employed the survey method with self-administrated questionnaires to answer several questions about individual and community empowerment of women. In-depth interview also, was applied to collect information about the NGOs in order to identify the NGOs activities, functions and its approaches. This study discovers that the activities of NGOs in Shiraz can be categorized into four functions: „developing individual ability‟; „educational functions‟; „awareness building‟;„mobilizing women to participate‟. The results were analyzed using some statistics i.e.,chi-square, one-way ANOVA and correlation. The finding shows that the level of women‟s empowerment is moderate among the women in Shiraz Iran. It means the women are never disempowered nor empowered sufficiently at the individual and community levels. Among the socio-economic status variables such as age, education, occupation, marital status and family income, marital status and education had significant relationship with women‟s empowerment. One-way ANOVA test showed that there was a statistically significant difference in the mean of women‟s empowerment among the four NGO‟s functions. The analysis of mean showed that the “mobilizing women” has a higher mean compare to other functions. There were also significant relationships between NGO‟s functions and three approaches (top-down, partnership and bottom-up). Further, one-way ANOVA showed that there was a significant difference in mean of women‟s empowerment among three approaches. The result revealed that the “bottom-up approach” had a higher effect on empowerment of women compared to two other approaches. Moreover, the results obtained from correlational analysis revealed that there was a positive relationship between level of participation and women‟s empowerment. The finding of this study has important implications for developing of empowerment particularly women in Iran. As result showed, the women empowered individually and collectively as they involved in NGOs activities. The findings of this study can contribute to empowerment literature and community development. Furthermore, the findings may also help NGOs and academic researchers to assess, monitor and evaluate the empowerment of women. The finding of this study could help NGOs‟ principals to improve their activities in order to raise the capabilities of NGOs toward the empowerment of women. To empower the women and to be meaningful their contribution, the study suggests that NGOs should expand their activities regarding to individual ability, educational functions, awareness building, and mobilizing women Moreover, the expected result could also help government agencies take into account some financial reforms that may be needed in the NGO sector.